Measurement of the CP asymmetry and branching fraction of B-0 ->rho K-0(0) - Aubert, B; Barate, R; Bona, M; Boutigny, D; Couderc, F; Karyotakis, Y; Lees, J; Poireau, V; Tisserand, V; Zghiche, A; Grauges, E; Palano, A; et al. (2007)
We present a measurement of the branching fraction and time-dependent CP asymmetry of B0→ρ0K0. The results are obtained from a data sample of 227×106 Υ(4S)→BB̄ decays collected with the BABAR detector at the PEP-II asymmetric-energy B factory at Stanford Linear Accelerator Center. From a time-dependent maximum likelihood fit yielding 111±19 signal events, we find B(B0→ρ0K0)=(4.9±0.8±0.9)×10-6, where the first error is statistical and the second systematic. We report the measurement of the CP parameters Sρ0KS0=0.20±0.52±0.24 and Cρ0KS0=0.64±0.41±0.20. © 2007 The American Physical Society.